Comparisons of Blood Parameters, Red Blood Cell Deformability and Circulating Nitric Oxide Between Males and Females Considering Hormonal Contraception: A Longitudinal Gender Study - Grau, Marijke; Cremer, John Maxwell; Schmeichel, Steffen; Kunkel, Markus; Bloch, Wilhelm (Frontiers in Physiology, 2018)
Red blood cell (RBC) deformability is an important determinant of the microcirculation. It is influenced by various hematological parameters but also by nitric oxide (NO) which is produced in RBC from L-arginine by RBC-NO synthase. Longitudinal studies on blood profile, deformability at rest and NO levels but also differences between males and females (+/- hormonal contraception; HC) are less known so far. The study thus aimed to investigate RBC deformability, RBC NO species (nitrite, RxNO), RBC L-arginine concentration and basal blood parameters in males and females (± HC) as a function of time. RBC deformability was measured at rest once per week and the remaining parameters were measured once per month, respectively. A second experiment aimed to daily measure RBC deformability and 17β-estradiol in Female +/- HC during a whole menstruation cycle to investigate a possible relation of the two parameters. Measured parameters showed low week-to-week variation and remained constant during study period. However, RBC deformability increased in Female + HC during study period possibly because of increasing training volume of the participants. Overall, results indicate gender differences in hematological parameters with higher RBC parameters (RBC count, hematocrit, hemoglobin concentration) in males compared to females. Differences were also observed between the female groups with Females – HC showing lower number of RBC but higher MCV and hematocrit compared to Females + HC. RBC deformability was highest in Females - HC which might be related to permanent higher estradiol levels and/or higher RBC NO levels because RBC nitrite and RBC RxNO concentrations were also highest in Females-HC. Results of the second experiment also suggest higher RBC deformability in Female – HC because of higher estradiol concentrations. L-arginine levels known to be related to RBC NO production were comparable in all groups. In conclusion, hematological, hemorheological and NO related parameters show gender differences. In particular, RBC deformability is affected by training volume and RBC estradiol concentrations. The results add new information on the complex regulation of RBC function which might help to better understand the role of RBC in the microcirculation.